MENINGKATKAN PRESTASI BELAJAR AKUNTANSI SISWA DALAM KOMPETENSI DASAR MENGELOLA KARTU PIUTANG DENGAN PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DI KELAS XI AKUNTANSI 2 SMK NEGERI 1 MUARA BUNGO: MENINGKATKAN PRESTASI BELAJAR AKUNTANSI SISWA DALAM KOMPETENSI DASAR MENGELOLA KARTU PIUTANG DENGAN PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DI KELAS XI AKUNTANSI 2 SMK NEGERI 1 MUARA BUNGO - TIA RA (LPPM Universitas Muhammadiyah Muara Bungo, 2020)
The background in this research is the achievement of Accounting Learning which is still low on the competence of Managing Accounts Receivable Cards, so that the daily test scores of students of class XI Accounting 2 SMK Negeri 1 Muara Bungo who have not reached the KKM. The purpose of this study is the Application of Problem Based Learning Learning Model Improving Accounting Learning Achievement in Class XI Accounting 2 SMK N. 1 Muara Bungo Students. This type of research is Classroom Action Research (PTK). The research setting consists of 1) research location 2) research time 3) research subjects. This research was conducted in two cycles. Cycle I had two meetings and cycle II had one meeting. The application of the Problem Based Learning Model to Improve Students' Accounting Learning Achievement in the Competency of Managing Accounts Receivable Cards for Class XI Accounting 2 SMK N. 1 Muara Bungo, can be said to be successful. The average value of students' accounting learning achievement before the action was taken was 69.36 with the KKM achievement percentage of 29%, after taking action in the first cycle the average value increased to 70.95 with the KKM achievement percentage of 54.17%. In the second cycle the students' average score increased to 93.86 or a percentage of 87.5% or an increase from the first cycle of 22.91.